The use of dynamic O-(2-18F-fluoroethyl)-l-tyrosine PET in the diagnosis of patients with progressive and recurrent glioma. Issue 9 (24th May 2015) - Galldiks, Norbert; Stoffels, Gabriele; Filss, Christian; Rapp, Marion; Blau, Tobias; Tscherpel, Caroline; Ceccon, Garry; Dunkl, Veronika; Weinzierl, Martin; Stoffel, Michael; Sabel, Michael; Fink, Gereon R.; et al.
Abstract: Background: We evaluated the diagnostic value of static and dynamic O -(2-[ 18 F]fluoroethyl)-l -tyrosine ( 18 F-FET) PET parameters in patients with progressive or recurrent glioma. Methods: We retrospectively analyzed 132 dynamic 18 F-FET PET and conventional MRI scans of 124 glioma patients (primary World Health Organization grade II, n = 55; grade III, n = 19; grade IV, n = 50; mean age, 52 ± 14 y). Patients had been referred for PET assessment with clinical signs and/or MRI findings suggestive of tumor progression or recurrence based on Response Assessment in Neuro-Oncology criteria. Maximum and mean tumor/brain ratios of 18 F-FET uptake were determined (20–40 min post-injection) as well as tracer uptake kinetics (ie, time to peak and patterns of the time–activity curves). Diagnoses were confirmed histologically (95%) or by clinical follow-up (5%). Diagnostic accuracies of PET and MR parameters for the detection of tumor progression or recurrence were evaluated by receiver operating characteristic analyses/chi-square test. Results: Tumor progression or recurrence could be diagnosed in 121 of 132 cases (92%). MRI and 18 F-FET PET findings were concordant in 84% and discordant in 16%. Compared with the diagnostic accuracy of conventional MRI to diagnose tumor progression or recurrence (85%), a higher accuracy (93%) was achieved by 18 F-FET PET when a mean tumor/brain ratio ≥2.0 or time to peak <45 min was present (sensitivity, 93%; specificity, 100%; accuracy, 93%; positive predictive value, 100%; P < .001). Conclusion: Static and dynamic 18 F-FET PET parameters differentiate progressive or recurrent glioma from treatment-related nonneoplastic changes with higher accuracy than conventional MRI.